Biallelic COA7-Variants Leading to Developmental Regression With Progressive Spasticity and Brain Atrophy in a Chinese Patient - Ban, Rui; Liu, Zhimei; Shimura, Masaru; Tong, Xiao; Wang, Junling; Yang, Lei; Xu, Manting; Xiao, Jing; Murayama, Kei; Elstner, Matthias; Prokisch, Holger; Fang, Fang (Frontiers in Genetics, 2021)
Objective The cytochrome c oxidase assembly factor 7 (COA7) gene encodes a protein localized to mitochondria that is involved in the assembly of mitochondrial respiratory chain complex IV. Here, we report the clinical, genetic and biochemical analysis of a female patient with suspected mitochondrial disorder and novel variants in COA7, that presented with a considerably different phenotype and age of onset than the five COA7 patients reported to date. Methods We performed trio-exome sequencing in the affected patient and both parents. To verify the pathogenicity of the detected variants in COA7, mitochondrial enzyme activities and oxygen consumption rate were investigated in fibroblasts of the patient and her parents. Results A Chinese girl was referred at the age of nine months with developmental delay and re-gression. In the following months, she lost previously acquired skills and developed progressive spasticity of the lower extremities. Trio-exome sequencing revealed compound heterzygous variants in COA7 (c.511G>A/p.Ala171Thr and c.566A>G/p.Asn189Ser). Functional validation experiments revealed isolated complex IV deficiency and a significantly reduced mitochondrial respiration rate in patient-derived fibroblasts. Interpretation Hitherto, characteristic features of COA7 patients were described as slowly progressing neuropathy and spinocerebellar ataxia, starting at the toddler age and progressing into adulthood. In contrast, our patient showed from three months of age developmental delay due to a rapidly progressive encephalopathy and brain atrophy. Unexpectedly, the ge-netic investigation revealed a COA7-associated mitochondrial disease, which was con-firmed functionally. Thus, this report broadens the genetic and clinical spectrum of this heterogeneous mitochondriopathy and highlights the value of the presented unbiased approach.